Cognitive functional approach to manage low back pain in rowers - Ng, L. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
There is a high prevalence of low back pain in rowers at all training levels. However, very few studies have reported an effective management strategy to reduce low back pain in these athletes. This may be due to the multidimensional nature of low back pain that ranges from physical, psychological, social and lifestyle factors. Recently, a Cognitive Functional approach to manage low back pain has been shown to reduce low back pain and disability in adolescent male rowers. This management strategy has been adapted and implemented to prevent LBP in elite international level rowers.